Microtonal Scordatura in the Guitar Works of A. Castilla-Ávila (1996-2021) - Castilla-Ávila, Agustín (Revista Vórtex, 2021)
In 1996, during my guitar studies, I read for the first time about microtonal guitars. I was so fascinated about it. Trying to experiment to hear microtones in my instrument, I created a 36EDO scordatura system, which I have been using now for 25 years. In this article, I would like to present my ideas in a personal and biographical way about how I decided to create my 36-divisions system and to compose with it. I would also like to explain about the challenges and the decisions I took as a composer during this time.